Factors affecting the Client's Performance in the Public Construction Projects: Case Study of Oman - A. AlBarami, Mohamed; Thiruchelvam, Sivadass; S.Ibrehem, Ahmmed (International Journal of Sustainable Construction Engineering and Technology, 2020)
Despite the vast research on construction projects management issues in the Middle-East, little is known about client involvement in public projects. This article presents a study on identifying significant factors affecting client participation performance in public construction projects in the Sultanate of Oman. The study was conducted in quantitative approach where the data was collected through questionnaire survey. The collected data was analysed statistically to determine the ranking of the identified factors based on the degree of involvement in the project. The study found that the handover phase had the highest client’s participation, while the operations and maintenance phase had the lowest client’s participation among all the five construction phases. The low client participation in any project has an undesirable influence on the projects’ overall outcomes. Consequently, this condition has harmed the time of completion of construction projects in the Sultanate of Oman. This condition is also the main reason for the quality problems in construction projects in Oman.